THE EFFECT OF TEMPERATURE AND BOILING TIME ON THE QUALITY OF KATSUOBUSHI (WOODY SMOKED FISH) SKIPJACK (Katsuwonus pelamis) - Nasution, Iqbal Naufal Khalis; Mus, Sukirno; Leksono, Tjipto (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRACTThis study was aimed to determine the effect of temperature and boiling time on the quality of katsuobushi skipjack (Katsuwonus pelamis) based on organoleptic test (appearance, aroma, texture, taste), proximate analysis (water, protein, ash, phenol, pH value) and microbiological test (Total Plate Count, fungi identification). The experimental design used in this study was a two factorial Completely Randomized Design (CRD) consisting of boiling temperature with 3 treatment levels, namely 70-80oC (S1), 81-90oC (S2), 91-100oC (S3) as the first factor, and time with 2 treatment levels, namely 30 minutes (L1) and 60 minutes (L2) as the second factor. The results showed that katsuobushi with treatment (S1L1) was the best treatment, indicated by the highest organoleptic quality with a value 8.12 and the characteristics clean, shiny color, no cracks; texture value 8.28 with the characteristics of hard, not easily broken; aroma value 7.64 with the specific characteristics of aroma scent without additional odor; taste value 7.69 with the characteristics of very tasty, savory; water content 11.94%, protein 78.95%, ash 0.56%, phenol 0.0013%, pH value 5.68, Total Plate Count 2.7 x 103 cfu/g and identification of fungi found in the type of Aspergillus sp. Keywords : boiling, katsuobushi, skipjack fish, temperature